Performance Evaluation of Concurrent Multipath Video Streaming in Multihomed Mobile Networks - James Nightingale; Qi Wang; Christos Grecos (International Journal of Digital Multimedia Broadcasting)
High-quality real-time video streaming to users in mobile networks is challenging due to the dynamically changing nature of the network paths, particularly the limited bandwidth and varying end-to-end delay. In this paper, we empirically investigate the performance of multipath streaming in the context of multihomed mobile networks. Existing schemes that make use of the aggregated bandwidth of multiple paths can overcome bandwidth limitations on a single path but suffer an efficiency penalty caused by retransmission of lost packets in reliable transport schemes or path switching overheads in unreliable transport schemes. This work focuses on the evaluation of schemes to permit concurrent use of multiple paths to deliver video streams. A comprehensive streaming framework for concurrent multipath video streaming is proposed and experimentally evaluated, using current state-of-the-art H.264 Scalable Video Coding (H.264/SVC) and the next generation High Efficiency Video Coding (HEVC) standards. It provides a valuable insight into the benefit of using such schemes in conjunction with encoder specific packet prioritisation mechanisms for quality-aware packet scheduling and scalable streaming. The remaining obstacles to deployment of concurrent multipath schemes are identified, and the challenges in realising HEVC based concurrent multipath streaming are highlighted.